Binding Analysis of Factor H Related Proteins with C3d - Muir, Aleesa (URJ-UCCS: Undergraduate Research Journal at UCCS, 2020)
The complement system is a major arm of the innate immune system which helps recognize foreign particles and clear them. Recognition of foreign particles is mediated in part by Factor H and Complement Factor H Related (CFHR) proteins. Dysregulation of Factor H and CFHR proteins can result in multiple diseases such as atypical hemolytic uremic syndrome (aHUS), C3 glomerulopathies, as well as other kidney diseases. aHUS is a rare condition that leads to end-stage renal disease in approximately 60% of patients (Skerka C, Chen Q, et a). Here we produced modified versions of mouse CFHR proteins using transfected mammalian cell lines. The CFHR proteins were then tested in binding affinity assays against a well characterized complement pathway protein, C3d. Initial studies showing binding indicate the need for further development of these related protein variants. These experiments can help us better understand how inflammation is controlled in the kidney and may help to identify novel therapeutic strategies.